Highly-accelerated volumetric brain examination using optimized wave-CAIPI encoding - Polak, Daniel; Bachert, Peter (Journal of magnetic resonance imaging, 2019)
Background Rapid volumetric imaging protocols could better utilize limited scanner resources. Purpose To develop and validate an optimized 6-minute high-resolution volumetric brain MRI examination using Wave-CAIPI encoding. Study Type Prospective. Population/Subjects Ten healthy subjects and 20 patients with a variety of intracranial pathologies. Field Strength/Sequence At 3 T, MPRAGE, T2-weighted SPACE, SPACE FLAIR, and SWI were acquired at 9-fold acceleration using Wave-CAIPI and for comparison at 2-4-fold acceleration using conventional GRAPPA. Assessment Extensive simulations were performed to optimize the Wave-CAIPI protocol and minimize both g-factor noise amplification and potential T1/T2 blurring artifacts. Moreover, refinements in the autocalibrated reconstruction of Wave-CAIPI were developed to ensure high-quality reconstructions in the presence of gradient imperfections. In a randomized and blinded fashion, three neuroradiologists assessed the diagnostic quality of the optimized 6-minute Wave-CAIPI exam and compared it to the roughly 3× slower GRAPPA accelerated protocol using both an individual and head-to-head analysis. Statistical Test A noninferiority test was used to test whether the diagnostic quality of Wave-CAIPI was noninferior to the GRAPPA acquisition, with a 15% noninferiority margin. Results Among all sequences, Wave-CAIPI achieved negligible g-factor noise amplification (gavg ≤ 1.04) and burring artifacts from T1/T2 relaxation. Improvements of our autocalibration approach for gradient imperfections enabled increased robustness to gradient mixing imperfections in tilted-field of view (FOV) prescriptions as well as variations in gradient and analog-to-digital converter (ADC) sampling rates. In the clinical evaluation, Wave-CAIPI achieved similar mean scores when compared with GRAPPA (MPRAGE: ØW = 4.03, ØG = 3.97; T2w SPACE: ØW = 4.00, ØG = 4.00; SPACE FLAIR: ØW = 3.97, ØG = 3.97; SWI: ØW = 3.93, ØG = 3.83) and was statistically noninferior (N = 30, P < 0.05 for all sequences). Data Conclusion The proposed volumetric brain exam retained comparable image quality when compared with the much longer conventional protocol. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:961-974.